(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study evaluates an internally developed strategic scenario aimed at revitalizing the Blue Oilfield, an offshore oil and gas field operated by Pertamina Hulu Energi Offshore South East Sumatra (PHE OSES), which currently facing high operating costs and declining production. Despite these challenges, the field remains economically promising. The proposed solution emphasizes renegotiation of Production Sharing Contract from Gross Split to Cost Recovery, cost optimization in surface facilities, selective reinvestment in drilling new infill wells, idle well reactivation, and workovers. The economical calculation of the proposed strategy was assessed through an integrated evaluation, combining capital budgeting, sensitivity analysis, and probabilistic modeling using Monte Carlo simulations. The findings reveal a strong financial outlook, with high Net Present Value (NPV) and consistent performance contract period. These results suggest that, with the right operational and contractual shifting, the Blue Oilfield has the potential to transition from a financial burden into a productive and value-added asset. This paper offers both a decision-making tool for stakeholders and a replicable model for similar brownfield revitalization efforts in Indonesia’s upstream sector.